1996
DOI: 10.1159/000203893
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Factor as a Survival and Growth Factor in Human Normal and Malignant Hematopoiesis

Abstract: Stem cell factor (SCF) is an essential hematopoietic cytokine that interacts with other cytokines to preserve the viability of hematopoietic stem and progenitor cells, to influence their entry into the cell cycle and to facilitate their proliferation and differentiation. SCF on its own cannot drive noncycling hematopoietic progenitor cells into the cell cycle but does prevent their apoptotic death. SCF when combined with other cytokines increases the cloning efficacy of hematopoietic progenitor cells from all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(56 citation statements)
references
References 35 publications
2
48
0
2
Order By: Relevance
“…6A and B, SCF triggered the activation of c-kit in both cell types, as demonstrated by an increase in the phospho-c-kit signal, and this consequently resulted in the phosphorylation of Erk. The SCF-c-kit pathway is well known as a promoter of migration in different types of stem cells such as hematopoietic (Hassan and Zander, 1996 for review), spermatogonial (Ohta et al, 2003) and neural stem cells (Jin et al, 2002;Erlandsson et al, 2004;Sun et al, 2004). We therefore examined the possibility that the activation of the c-kit pathway led to a similar functional effect, in addition to the increased kinase activity detected biochemically.…”
Section: Involvement Of the Stem Cell Factormentioning
confidence: 99%
“…6A and B, SCF triggered the activation of c-kit in both cell types, as demonstrated by an increase in the phospho-c-kit signal, and this consequently resulted in the phosphorylation of Erk. The SCF-c-kit pathway is well known as a promoter of migration in different types of stem cells such as hematopoietic (Hassan and Zander, 1996 for review), spermatogonial (Ohta et al, 2003) and neural stem cells (Jin et al, 2002;Erlandsson et al, 2004;Sun et al, 2004). We therefore examined the possibility that the activation of the c-kit pathway led to a similar functional effect, in addition to the increased kinase activity detected biochemically.…”
Section: Involvement Of the Stem Cell Factormentioning
confidence: 99%
“…Accordingly, SCF has been shown to promote proliferation and differentiation of early progenitor cells, as well as to increase their survival, while at the same time exerting its effects on mature mast cells from different tissues. 14,15 Previous studies have shown that once administered in combination with other cytokines such as G-CSF, SCF has a synergistic effect on enhancing mobilization of CD34 ϩ HPCs into the PB. 16 Accordingly, accumulating evidence exists that the combined use of G-CSF and SCF is associated with higher mobilization rates as compared to G-CSF alone.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Moreover, SCF has become an alternative agent in patients who show a poor response to other mobilization protocols. Although the biological and clinical effects of SCF administration have been extensively explored, 14,20 information is still scanty on the impact of administration of SCF combined with other cytokines and/or chemotherapy on the relative composition of both the CD34 ϩ and CD34 Ϫ cell subsets some of which have a potentially important role in predicting the outcome of either autologous or allogeneic transplants; these include the subsets of more immature CD34 ϩ HPC and DC, among others. 21,22 The aim of the present study was to gain further insights into the effects of the use of SCF in combination with G-CSF and cyclophosphamide.…”
Section: Introductionmentioning
confidence: 99%
“…Human bone marrow stroma is responsible for supporting both the daily production of billions of mature blood cells [1] and the generation of osteoblasts [2,3], the major contributor to bone formation from CD34 + marrow stem/progenitor cells [4,5]. Ultrastructural and developmental studies have also demonstrated the close physical association between endosteal osteoblasts and hemopoietic marrow cells in the bone marrow (BM) cavity [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, normal human osteoblasts produce several hemopoietic cytokines, including G-CSF [9], macrophage colony-stimulating factor (M-CSF) [10], interleukin 6 (IL-6) [11], tumor necrosis factor-alpha (TNF-α) [12], leukemia inhibitory factor (LIF) [13] and osteoclast differentiation factor (ODF) [14] as well as GM-CSF and IL-8 upon IL-1 stimulation [15]. These cytokines are required for both hemopoiesis [1] and the generation of osteoclasts for bone modulation from peripheral blood [14,16,17], cord blood [18], and BM [19] cells. Also, allogeneic transplantation of a donor-derived bone graft along with BM stem/progenitor cells in mice has promoted complete hemopoietic reconstitution and improved immune reconstitution after transplants in a chimeric-resistant combination [20][21][22][23], indicating a clear facilitating role for osteoblasts in allogeneic bone marrow transplantation (BMT).…”
Section: Introductionmentioning
confidence: 99%